Systematic Literatur Review Perkembangan Pembelajaran Gamifikasi dalam Pembelajaran Ekonomi - Saady, Farma Ladia; Suryadi, Edi; Machmud, Amir (Universitas Pendidikan Ganesha, 2024)
Gamification has emerged as an approach that can increase student engagement and motivation in economics learning. The aim of this research is to conduct a systematic review of existing literature regarding the development of gamification in economic learning and then obtain a distribution for 2020-2024. The data collection technique is carried out by downloading files on the Scopus database to see trends in publications with the largest number, number of documents, ranking classifications of institutions or universities, journals and documents, as well as the use of shared keywords. The method used is bibliometric analysis. A total of 32 documents were collected through the Scopus database and then combined into one file in ris format and entered into the VOSviewer application to obtain network visualization and overlay visualization. The research results show that the trend of publications related to gamification learning in economics learning has increased from year to year. The largest number of documents is in